Selection of contractor by Using Analytical Hierarchy Process (AHP) - Putri Zulaiha, Razi; Noram Irwan, Ramli; Putra Jaya, Ramadhansyah; Mohamad Idris, Ali (IOP Publishing, 2020)
Construction projects is progressing rapidly in Malaysia and have been as one of an important factor in contributing the boost of country's economic. Well known as a sectors with involvement of multiple players, thus, contractor selection is an important aspect in construction sector especially for client or parties involve that need to hire the best contractor to manage and complete their project within time-line and bearable cost couple with comprised quality. Furthermore, without a suitable method use in selection of contractor, it will affect the completion of whole project. This paper aiming in make use of the analytical hierarchy process (AHP) as a decision support model to select contractor. The AHP allows constructing decision as hierarchies and each criterion can be evaluated through weighted determined by the expert in construction field. The objectives of this study is to develop the main criteria used by client in selection of contractors also identify the weighted criteria by using AHP method from current practice in Malaysia. Besides, this method is one of the decision-making that is necessary to eliminate the risks of project failure due to poor contractor's performance.